The Etiology of Vaginal Discharge Syndrome in Zimbabwe: Results from the Zimbabwe STI Etiology Study. Issue 6 (June 2018) - Chirenje, Z. Mike; Dhibi, Nicholas; Handsfield, H. Hunter; Gonese, Elizabeth; Tippett Barr, Beth; Gwanzura, Lovemore; Latif, Ahmed S.; Maseko, Dumisili Venessa; Kularatne, Ranmini S.; Tshimanga, Mufuta; Kilmarx, Peter H.; Machiha, Anna; et al.
Abstract : Introduction: Symptomatic vaginal discharge is a common gynecological condition managed syndromically in most developing countries. In Zimbabwe, women presenting with symptomatic vaginal discharge are treated with empirical regimens that commonly cover both sexually transmitted infections (STIs) and reproductive tract infections, typically including a combination of an intramuscular injection of kanamycin, and oral doxycycline and metronidazole regimens. This study was conducted to determine the current etiology of symptomatic vaginal discharge and assess adequacy of current syndromic management guidelines. Methods: We enrolled 200 women with symptomatic vaginal discharge presenting at 6 STI clinics in Zimbabwe. Microscopy was used to detect bacterial vaginosis and yeast infection. Nucleic acid amplifications tests were used to detect Neisseria gonorrhoeae, Chlamydia trachomatis, Trichomonas vaginalis, and Mycoplasma genitalium . In addition, serologic testing was performed to detect human immunodeficiency virus (HIV) infection. Results: Of the 200 women, 146 (73%) had an etiology detected, including bacterial vaginosis (24.7%); N. gonorrhoeae (24.0%); yeast infection (20.7%); T. vaginalis (19.0%); C. trachomatis (14.0%) and M. genitalium (7.0%). Among women with STIs (N = 90), 62 (68.9%) had a single infection, 18 (20.0%) had a dual infection, and 10 (11.1%) had 3 infections. Of 158 women who consented to HIV testing, 64 (40.5%) were HIV infected. The syndromic management regimen covered 115 (57.5%) of the women in the sample who had gonorrhea, chlamydia, M. genitalium, or bacterial vaginosis, whereas 85 (42.5%) of women were treated without such diagnosis. Conclusions: Among women presenting with symptomatic vaginal discharge, bacterial vaginosis was the most common etiology, and gonorrhea was the most frequently detected STI. The current syndromic management algorithm is suboptimal for coverage of women presenting with symptomatic vaginal discharge; addition of point of care testing could compliment the effectiveness of the syndromic approach. Abstract : Among women presenting with symptomatic vaginal discharge at primary health clinics in Zimbabwe, bacterial vaginosis (24.7%) and Neisseria gonorrhoeae infection (24%) were the most common etiologies.